Faecal characteristics and milk production of dairy cows in early-lactation fed diets differing in forage types in commercial herds. (2nd January 2016) - Mgbeahuruike, A. C.; Nørgaard, P.; Eriksson, T.; Nordqvist, M.; Nadeau, E.
ABSTRACT: Effects of grass–clover silage (GCS) alone or combined with whole-crop cereal silage, maize silage (MS) or ensiled pressed sugar beet pulp (EPSB) on faecal characteristics and performance of early-lactation dairy cows were studied in 26 herds. Data were analysed with herd as the experimental unit and correlation coefficients among the variables were estimated. Feeding MS combined with GCS resulted in faeces of a firmer consistency ( P < .05), containing more undigested fibre compared to feeding GCS alone or with EPSB ( P < .05). There was a strong positive correlation between the number of grains and starch concentration in faeces ( r = 0.83, P < .001). Increasing forage dry matter (DM) intake decreased faecal DM concentration ( r = −0.54, P < .01) but seems to result in cleaner cows, whereas increasing DM intake of concentrate increased faecal DM concentration ( r = 0.63, P < .01) but might result in dirtier cows.